Hypoxia, hypercarbia, and mortality reporting in studies of anaesthesia-related neonatal neurodevelopmental delay in rodent models: A systematic review. Issue 2 (February 2020) - Floyd, Thomas F.; Khmara, Kseniya; Lamm, Ryan; Seidman, Peggy
Abstract : BACKGROUND: The concept of anaesthesia-related neonatal neurotoxicity originated in neonatal rodent models, yet prospective clinical studies have largely not supported this concern. OBJECTIVES: To determine the frequency and magnitude of hypercarbia, hypoxia and death in rodent models of neonatal anaesthetic toxicity and neurodevelopmental delay. DESIGN: Systematic review of published rodent studies of neonatal anaesthesia neurotoxicity. We documented anaesthetic, route, dose, frequency and duration of exposures. We further report ventilation method, documentation of adequacy of ventilation [arterial blood gas (ABG), other], mortality and the reporting of mortality. DATA SOURCES: A PubMed literature search from 2003 to 2017 was conducted to identify studies on neurotoxicity in neonatal rodent models. ELIGIBILITY: Studies were included when at least one group of animals fell within the postnatal age range of 3 to 15 days. Only English language original studies published as full-length articles in peer reviewed journals were included in the final analysis. RESULTS: One hundred and three manuscripts were included. Ninety-eight percent of studies were conducted using spontaneous ventilation (101/103), with ABG monitoring used in only 33% of studies and visual monitoring alone for respiratory distress or cyanosis was employed in 60%. Of the 33% who reported ABG results, there were widely divergent values, with most reporting modest-to-severe hypercarbia. Mortality (median 11%, range of 0 to 40%), which infers severe hypoxia, was documented in only 36/103 (35%) reports. CONCLUSION: Hypoxia and hypercarbia have known apoptotic effects on developing brains. Hence, the inadequate control of hypercarbia and hypoxia in neonatal rodent models of anaesthetic exposure during spontaneous ventilation suggests that the evidence for developmental delay and neurotoxicity attributed to anaesthesia may not be valid in humans.